Childhood asthma and indoor allergens in Native Americans in New York - Tarbell Alice; Carpenter David O; Montoya Lupita D; Surdu Simona (BMC, 2006)
Abstract Background The objective of this study was to assess the correlation between childhood asthma and potential risk factors, especially exposure to indoor allergens, in a Native American population. Methods A case-control study of St. Regis Mohawk tribe children ages 2-14 years, 25 diagnosed with asthma and 25 controls was conducted. Exposure was assessed based on a personal interview and measurement of mite and cat allergens (Der p 1, Fel d 1) in indoor dust. Results A non-significant increased risk of childhood asthma was associated with self-reported family history of asthma, childhood environmental tobacco smoke exposure, and air pollution. There was a significant protective effect of breastfeeding against current asthma in children less than 14 years (5.2 fold lower risk). About 80% of dust mite and 15% of cat allergen samples were above the threshold values for sensitization of 2 and 1 μg/g, respectively. The association between current asthma and exposure to dust mite and cat allergens was positive but not statistically significant. Conclusion This research identified several potential indoor and outdoor risk factors for asthma in Mohawks homes, of which avoidance may reduce or delay the development of asthma in susceptible individuals.